Phosphated fertilization with organic and inorganic amendments in corn crops (Zea mays L.) - Duarte-Monzón, Alder-Delosantos; González-Caceres, Eugenio; Rasche-Álvarez, Jimmy Walter; Leguizamón-Rojas, Carlos; Fatecha-Fois, Diego-Augusto (Revista de Ciencias Agrícolas, 2020)
The limited availability of phosphorus in most soils in the eastern region of Paraguay restricts the productivity of the chipa corn, where fertilization with phosphates soluble could be one of the alternatives to make up the shortfall nutritional of cultivation. In addition, the combination with amendments makes the use of inorganic fertilizers more efficient in this production system. The work was carried out in the town of Ybyrarobana, Canindeyú, with the aim of to evaluate the effects of phosphorus doses, in combination with organic and inorganic amendments, on corn production. The treatments were distributed in split-plots under a randomized complete block design with 4 blocks. The amendments (bovine manure and ash) and the control occupied the main plots and the doses of P2 O5 (0, 40, 80, 120 and 160kg ha-1) the subplots. Variables such as post-harvest soil fertility, crop growth and yield were determined. The data were subjected to ANOVA and pair-wise comparisons by the Tukey´s test with 5% of probability. Except for the spike length, the evaluated variables showed significant differences between the amendments used. However, there were no statistical differences among doses of P2O5. The application of bovine manure and soybean expeller ash increased the pH and exchangeable potassium, and decreased exchangeable aluminum, while the levels of calcium, magnesium and phosphorus were not influenced.